Glycine confers neuroprotection through microRNA-301a/PTEN signaling. Issue 1 (December 2016) - Chen, Juan; Zhuang, Yang; Zhang, Zhi-Feng; Wang, Shu; Jin, Ping; He, Chunjiang; Hu, Peng-Chao; Wang, Ze-Fen; Li, Zhi-Qiang; Xia, Guang-Ming; Li, Gang; Wang, Yuan; et al.
Abstract Background Glycine is known to protect against neuronal death. However, the underlying mechanism remains to be elucidated. The microRNA-301a is involved in both biological and pathological processes. But it is not known whether microRNA-301a has a neuroprotective property. In this study, we aimed to determine whether glycine-induced neuroprotection requires microRNA-301a-dependent signaling. Results We provided the first evidence that glycine increased the expression of microRNA-301a in cultured rat cortical neurons and protected against cortical neuronal death through up-regulation of microRNA-301a after oxygen-glucose deprivation. MicroRNA-301a directly bound the predicted 3′UTR target sites of PTEN and reduced PTEN expression in cortical neurons. We revealed that PTEN down-regulation by microRNA-301a mediated glycine-induced neuroprotective effect following oxygen-glucose deprivation. Conclusions Our results suggest that 1) microRNA-301a is neuroprotective in oxygen-glucose deprivation-induced neuronal injury; 2) glycine is an upstream regulator of microRNA-301a; 3) glycine confers neuroprotection through microRNA-301a/PTEN signal pathway.